Medical Students’ Knowledge of Osteoporosis in Ege University Faculty of Medicine - Sibel Eyigör; Hale Karapolat; Berrin Durmaz (Archives of Rheumatology, 2008)
Objective: Osteoporosis is a major public health problem in many countries. Educating healthcare providers about osteoporosis may play a pivotal role in improving osteoporosis management. However, there are very few studies at the physicians’ level of knowledge on this matter. Our aim was to determine as future physicians, Turkish medical students’ knowledge and attitudes to the management and prevention of osteoporosis. Materials and Methods: A total of 375 medical students from each grade were asked to fill in a questionnaire about osteoporosis. Results: 98.9% of the students surveyed thought they were somewhat familiar with osteoporosis. Only 0.3% of the medical students who completed the questionnaire answered all the questions on the risk factors for osteoporosis correctly. The fact that supplementary medications in addition to calcium are needed for the management of osteoporosis was known by 45.9% of the medical students. With 10.7%, very few students knew that osteoporosis is directly responsible of hip fractures. On the other hand, 18.9% of the students knew that the disease could result in fatality. Conclusion: The results of the present study show that medical students know the definition of osteoporosis but their knowledge on complications and preventive measures were insufficient in all classes. During their medical education, medical students should be furnished with necessary information on risk factors for osteoporosis and preventive measures that are applicable to the community and this knowledge should allow them to plan effective ways of using information. (Rheumatism 2008; 23: 77-81)